1982
DOI: 10.1111/j.1469-8137.1982.tb03365.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inoculation of White Clover With Mycorrhizal Fungi in Unsterile Hill Soils

Abstract: SUMMARYThe response of two cultivars of white clover (Aberystwyth SI 84 and New Zealand Grasslands Huia), grown under laboratory and field conditions, to inoculation with two endophytes (Glomus mosseae LI and Glomus etunicatus) was investigated in two hill soils with various amounts of added phosphate.In the experiment with the deep peat soil in the laboratory, inoculation with either endophyte increased infection from 2 % to up to 70 %, the increase being less the higher the amount of added P. Shoot growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…Similar results were obtained by [12]. Rangeley et al [16] have also reported that colonization of root is directly proportional to root growth.…”
Section: Discussionsupporting
confidence: 85%
“…Similar results were obtained by [12]. Rangeley et al [16] have also reported that colonization of root is directly proportional to root growth.…”
Section: Discussionsupporting
confidence: 85%
“…These responses occurred despite the introduction of the fungi at sowing, probable competition from and beneficial effects of the indigenous species, and the widely differing natural fertilities of the experimental sites. These results and those of Rangeley et al (1982) therefore demonstrate that responses to inoculant VAM fungi can be obtained in pastoral agriculture and are sufficiently encouraging for them to be pursued further with a view to their possible commercial exploitation.…”
Section: Discussionmentioning
confidence: 57%
“…Some VAM fungi stimulate growth only over a limited range of soil phosphorus contents (Abbott &Robson, 1977;Hayman&Mosse, 1979;Rangeley et al 1982). For example in Rangeley et al's (1982) field experiments, inoculation with Glomus etunicatus Becker & Gerdemann produced growth responses only when 40 kg P/ha had also been applied.…”
Section: Measurementsmentioning
confidence: 99%
“…Such introductions are not, however, always successful. Rangeley et al (1982) obtained no effect on dry matter production of Trifolium repens in response to introduction of North African isolate of Glomns mosseae (Nicol. & Cierd.)…”
Section: Discussionmentioning
confidence: 97%